2022
DOI: 10.1007/s10661-022-10430-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of change in the peat soil properties affected by different fire severities

Abstract: Tropical peatland ecosystems of Indonesia provide direct economic bene ts to the local communities and act to maintain the local weather patterns. The impact of burning tropical peat swamp forests of land clearing for palm oil plantations can have signi cant consequences on the change in the characteristics of peat soil. The aim of this study was to determine the physical, chemical, and biological properties of the peat soils by the eld and laboratory testing and analysis for understanding a change in the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 103 publications
0
0
0
Order By: Relevance
“…Study by [15] observed the effect of a peat fire in 2019 in South Sumatra display that the ash content increased 57% and also improved the soil pH [16]. Moreover, other study showed that peat fires decrease water retention capacity by 1 -12% [17]. Peatland fires that particularly affecting soil characteristics occur yearly in the South Kalimantan Province Indonesia.…”
Section: Introductionmentioning
confidence: 98%
“…Study by [15] observed the effect of a peat fire in 2019 in South Sumatra display that the ash content increased 57% and also improved the soil pH [16]. Moreover, other study showed that peat fires decrease water retention capacity by 1 -12% [17]. Peatland fires that particularly affecting soil characteristics occur yearly in the South Kalimantan Province Indonesia.…”
Section: Introductionmentioning
confidence: 98%